EFEKTIFITAS MEDIA RUMAH BILANGAN UNTUK MENINGKATKAN KEMAMPUAN MENGENAL NILAI TEMPAT BILANGAN BAGI ANAK KESULITAN BELAJAR - Rati Purwasih (Jurnal Penelitian Pendidikan Khusus, 2014)
Abstract: This research is motivated by problems that researchers in the field discovered that the child is a learning disability X grade III who have difficulty in determining the place value of numbers. This study aims to improve the ability to recognize vowels learning disability child grade III using the medium of Number Home. This research is a Single Subject Research (SSR). The design of this study A-B-A. In the baseline condition could only scored 0%, in the intervention condition (B) 100%, whereas in the baseline condition (A2) after intervention no longer given where the child is better able to determining the place value of numbers and child obtain a score of 100%. Kata-kata kunci : Media Rumah Bilangan; nilai tempat; anak kesulitan belajar